Lessons that can be learned from the SARS-CoV-2 pandemic and their impact on the prophylaxis and treatment development for neglected tropical arboviruses - Danilo Rosa-Nunes; Danilo B. M. Lucchi; Robert Andreata-Santos; Luiz Mario R. Janini; Carla Torres Braconi (Frontiers in Drug Discovery, 2023)
In the 21st Century, emergence and re-emergence of infectious diseases is significant and has an increasing importance in global concern of public health. Based on the COVID-19 pandemic and recently reported epidemics, most human pathogens originate in zoonosis. Many of such pathogens are related to viruses that have RNA genomes, which can be presented structurally as a single-strand or double-strand. During the last two decades, a timeline of major RNA viruses emergencies can be exemplified, such as Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) in 2003, influenza A virus (H1N1) pdm09 in 2009, Middle East respiratory syndrome coronavirus (MERS-CoV) in 2012, Ebola virus (EBOV) in 2013–2016, Zika virus (ZIKV) in 2015 and the SARS-CoV-2 pdm19 in 2019. Even so, prophylactic or therapeutic drugs are unavailable for many RNA viruses circulating. Nonetheless, the COVID-19 pandemic brought considerable scientific advances in accelerating progress regarding prophylaxis, antiviral and drug development, and novel treatments. Regarding RNA virus diseases for humans, arboviruses play an essential and neglected role, constantly reemerging and affecting almost half of the human population, for which no drug has been licensed. Here we review the consolidated RNA viruses’ emergence and re-emergence in the 21st Century through available data. Then, we explored valuable lessons gained during the SARS-CoV-2 pandemic and focused on potential epidemiologic updates, prophylaxis, available treatments, and viral drug inhibitors. Finally, we explore arbovirus’s significance and the ongoing development of effective vaccines, antiviral drugs, and novel therapeutic approaches as strategies to control these neglected tropical diseases (NTD).